District Energy Trends, Issues, and Opportunities : The Role of the World Bank - Gochenour, Carolyn (Washington, DC: World Bank, 2013)
This study reviews the history and development of district heating and district cooling, together referred to as district energy in North America, Western Europe, Asia, Eastern and Central Europe, and the Former Soviet Union (FSU). Experience from other parts of the world where DH systems exist could be beneficial to DH industry managers and regulators in Eastern and Central Europe and FSU countries in modernizing their management systems and improving their policies and practices to allow for the attraction of capital that is urgently needed. The report reviews, in a systematic manner, the key institutional, economic, financial, technical, and environmental issues in the countries of Eastern and Central Europe and the FSU with the goal of arriving at operationally relevant issues and defining the awareness and understanding of the nature of activities which can lead to increasing energy efficiency and the attractiveness of district energy to private financing.